The resources and governance of non-governmental organizations in Uganda - Barr, A; Fafchamps, M; Owens, T (CSAE (University of Oxford), 2004)
Using original survey data, we document the activities, resources, and governance structure of NGOs operating in Uganda. The NGO sector is funded primarily by international non-governmental organizations and bilateral donors. We find large differences in size and funding across NGOs, with only a few NGOs attracting most of the funding. Most NGOs are small and underfunded and focus on raising awareness and advocacy. Few NGOs are faith-based. Most screening and monitoring is done by grant agencies. Some monitoring is also done internally by members and trustees. Few respondents were able to provide coherent financial accounts. Reporting requirements appear onerous given the limited organizational capacity of Ugandan NGOs.